Topology Optimization of Car Doorstep Using Simulation Method - Karohika, I Made Gatot; Rimasfirli, Muhammad Farizqi; Widiyarta, I Made; Antara, I Nyoman Gde; Mogi, I Komang Ari (International Journal of Integrated Engineering, 2024)
The Car doorstep is a device designed to facilitate access to the roof of a car. It is a sturdy tool capable of supporting human weight while lifting items onto the car’s roof. In this study, the car doorstep was made using waste drum brake shoe material, and its mass was reduced through static structural simulation and topology optimization in Ansys Workbench. The objective was to achieve reduced mass, total deformation, equivalent stress, maximum principal stress, and safety factors for each variation. The car doorstep's geometry was subjected to a load of 1765 N and appropriate supports were applied. Based on the conducted research, the car door step's geometry with a 40% variation resulted in the most optimal data, with the following values: mass (1,4 Kg), total deformation (1.81 mm), equivalent stress (21.47 MPa), maximum principal stress (22.17 MPa), and safety factor (yield strength: 1.2, ultimate strength: 4.54)